METHODEN ZUR BILDUNG DER SCHREIBFÄHIGKEITEN IN FREMDSPRACHEN (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The article deals with the formation of written language skills, which is one of the current problems. Opportunities for improvement, reasons for the decline in literacy, measures to prevent it, the use of dialect-specific words in the language and the influence of the external environment on it are discussed in detail